FEATURED FOOD COMMODITIES FOR FOOD SECURITY SUPPORT IN BALI PROVINCE, INDONESIA - Made Antara; Made Sri Sumarniasih (Socio-Economics/Agribusiness Department, 2020)
Food availability in a region is local food production added imported food and food stock in the warehouse logistics agency. While local food production is supported by featured food production in the region. The objectives of the research: (1) Food availability in Bali Province, (2) the level of regional food security in Bali Province, and (3) featured food commodities in Bali Province. The results of the research showed that (1) Food availability in Bali Province namely the availability of carbohydrate source are 202 kg/cap/yr, protein are 112 kg/cap/yr, vitamins and minerals are 117 kg/cap/yr for 2017, which means it is all beyond the standard FAO food requirements; (2) Bali's regional food security from the perspective of energy availability is guaranteed to be assured, proved by higher energy availability compared to the adequacy for energy; (3) Featured food commodities in Bali Province is rice potential are developed in districts of Jembrana, Tabanan, Badung, Denpasar, Gianyar and Buleleng. Corn, cassava, and peanut potential are developed in districts of Klungkung, Bangli and Karangasem. Soybean in districts of Jembrana, Tabanan, Badung, Gianyar, Klungkung, Denpasar. Peanuts in districts of Bangli, Karangasem and Buleleng, Green bean in districts of Gianyar, Karangasem and Buleleng. Beef food sources potential are developed in all districts in Bali, a source of protein chicken meat in districts of Bangli, Karangasem and Tabanan. Food sources of fruits in districts of Jembrana, Bangli, Karangasem and Buleleng. Vegetables potential are developed in districts of Tabanan, Klungkung and Denpasar to support Bali's regional food security.